Influence of Family Environment toward Moral of Grade 4 Students KMI in Pondok Modern Darussalam Gontor for Girls 3 - Miftahul Ulum; Seyn Octavia Nurhanif (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Islamic education directing human behavior and work in accordance with the laws of God, Gontor For Girls Campus 3 is the institution which forms his or her students in order to cling to God and Islam good character with a strong discipline, when the students adhere to the discipline is there then indirectly will shape the character of the students, but if the home State does not support, then it will affect all on the character of the students class 4. The purpose in writing is to know the State of the family environment as well as the character of the students class 4 and or no influence between them. The method of this research is the Research field with the type of Quantitative Associative Causal analysis techniques, and use Product moment. Final results of the research indicate: (1) The State of the family environment of the student class 4 achieved an average of 69.8 with high quality, (2) The character of the students class 4 any good by reaching an average of 64.6 with high quality, (3) Presence of influence from family environment against the character of the students Class 4, with outcomes percentage rxy 0.427 by looking at the average value on the